Study of prevalence of heart disease in antenatal mothers along with fetal and maternal outcome from a tertiary care hospital, Salem, Tamil Nadu, India - Sengodan, Subha Sivagami; Selvaraj, Shobhika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Incidence of pregnancy in women with heart disease is increasing due to the increasing number of women with congenital heart disease. Although most cardiac conditions are well tolerated during pregnancy, there are some conditions that have adverse fetal and maternal outcome. Objective of this study is to study the prevalence of heart disease in antenatal mothers and fetal outcome with obstetric management. Methods: This is a prospective observational study carried out in the Department of Obstetrics and Gynaecology at Government Mohan Kumaramangalam Medical College and Hospital during January 2018 to March 2019 for a period of fifteen months. Authors included 149 antenatal mothers with heart disease and analysed the data using percentage analysis through excel software. Results: Incidence of heart disease in pregnancy was observed to be 1.2%. Rheumatic heart disease being 73.8%, congenital being 22.8% and complete heart block was 3.4%. Among rheumatic heart disease mitral stenosis was the most common lesion. Atrial septal defect was the most common congenital heart disease. The mean gestational age of delivery was 37 to 38 weeks. 58% delivered by vaginal route. Most common neonatal complication was prematurity. Pregnancy and neonatal outcome were favorable. Conclusions: Heart disease complicating pregnancy has increased due to late marriage, obesity, hypertension and diabetes. Early referral, regular follow-up and multi-disciplinary approach with tertiary care back-up will bring a favorable maternal and neonatal outcome in patients with heart disease.